Factors That Motivate and Militate Undocumented Migrants to Vaccinate Their Children in Sabah, Malaysia - Michal Christina; Mohd Yusof Ibrahim; Haryati Abdul Karim; Prabakaran Dhanaraj (Scientific Foundation SPIROSKI, 2023)
BACKGROUND: Undocumented migrant families face many challenges in bringing their children for vaccination. The recent outbreak of poliomyelitis in Sabah among undocumented migrant children highlights the gap in vaccination coverage among these populations. AIM: This study aimed to determine the factors that influence undocumented migrants in Sabah to vaccinate their children. METHODS: This is a cross-sectional study using a questionnaire developed based on the findings from a qualitative study. This study was conducted in 15 districts of Sabah among the mothers of undocumented migrant children. Multiple Logistic Regression was done to find out the significant factors that influence undocumented migrants to vaccinate their children. RESULTS: A total of 942 responses were collected during the study. About 78.7% of the respondents attended health facilities to vaccinate their children. Only the legal status of the undocumented migrant (adjusted odds ratio [aOR] = 0.15 [95% CI: 0.52– 0.43]) remains a significant militating factor for undocumented migrants to vaccinate their children. Two factors, parental trust in health-care providers and vaccines (aOR = 18.24 [95% CI: 8.42–39.51]) and good support system (aOR = 2.65 [95% CI: 1.77–3.97]), remain significant motivating factors that influence undocumented migrants to vaccinate their children. Those who had visited the health facilities for an antenatal check-up (aOR = 25.93 [95% CI: 17.07–39.39]) and delivery (aOR = 93.63 [95% CI: 34.77–257.81]), with income of more than RM 1000 (aOR = 6.09 [95% CI: 3.66–10.12]) have a higher prevalence to bring their children for vaccination. CONCLUSION: In the best interest of public health and to prevent the further re-emergence of vaccine-preventable diseases in Sabah, it is important to address these factors to improve vaccine uptake among undocumented migrant children.